The organizational climate and its relationship with teaching performance in the I.E. N ° 5175 "Manuel Arévalo Cáceres". Ugel 04 - Ancón. Lima 2017 - Abrigo Domínguez, Eleuterio (2018)
The scientific research we have done is basic, correlational, non-experimental causal. The factors of study are two: The organizational climate and the teaching performance of the Educational Institution N ° 5175 "Manuel Arévalo Cáceres" UGEL 04- Ancón. Lime. 2018. The population and sample was conformed by the students of the Educational Institution N ° 5175 "Manuel Arévalo Cáceres". The design of the research is transectional, correlational, causal, bivariate, transversal. For the collection of data, two structured questionnaires were drawn up as a measurement, as well as an observation form, an interview with the students. The variable organizational climate consists of the following dimensions: management style, leadership, communication levels, conflict management. Similarly, the variable teacher performance consists of the following dimensions: methodological strategies, planning of teaching, use of educational media and materials, professional solvency. The sample consisted of 112 students of the Educational Institution N ° 5175 "Manuel Arévalo Cáceres" UGEL 04- Ancón. Lime. 2018 The instruments comply with the qualities of validity and reliability. The study proposes the following research hypothesis: the Organizational Climate is related to the Teaching Performance in the Educational Institution N ° 5175 "Manuel Arévalo Cáceres" UGEL 04- Ancón. Lime. 2018 The obtained results allow us to reject the null hypothesis and accept the hypothesis investigated since it has been found according to the Spearman's Rho correlation of 0.538 is MODERATE association of the variables and being highly significant. In addition, according to the evidence of independence (*** p <.000) highly significant, the research hypothesis is accepted: There is a direct and significant relationship between the Organizational Climate and the Teaching Performance in the Educational Institution N ° 5175 "Manuel Arévalo Cáceres" UGEL 04- Ancón. Lime. 2018